2010
DOI: 10.1088/0953-2048/23/4/045025
|View full text |Cite
|
Sign up to set email alerts
|

Development of 1.5 THz waveguide NbTiN superconducting hot electron bolometer mixers

Abstract: We present a characterization of a 1.5 THz waveguide niobium titanium nitride (NbTiN) superconducting hot electron bolometer (HEB) mixer which can be pumped by a commercial solid state tunable local oscillator (LO) source. The NbTiN HEB mixer is made from a 12 nm thick NbTiN thin film deposited on a quartz substrate at room temperature. A gold electrode is formed in situ on the NbTiN thin film without breaking vacuum to ensure good contact. The uncorrected DSB receiver noise temperature is measured to be 1700 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 19 publications
3
25
0
Order By: Relevance
“…The simulated IF gain bandwidth is 2.7 GHz at the optimum bias point. Hence we have confirmed that fairly good performance can be obtained at 1.5 THz even with the 10.8 nm NbTiN film which is thicker than that used by the other groups (a few nm) for the phonon-cooled mixers [14], improving our previous result at 1.5 THz after optimizing the RF matching circuit [6]. By using the in situ fabrication process, we obtain the above performance by use of a 10.8 nm NbTiN film.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The simulated IF gain bandwidth is 2.7 GHz at the optimum bias point. Hence we have confirmed that fairly good performance can be obtained at 1.5 THz even with the 10.8 nm NbTiN film which is thicker than that used by the other groups (a few nm) for the phonon-cooled mixers [14], improving our previous result at 1.5 THz after optimizing the RF matching circuit [6]. By using the in situ fabrication process, we obtain the above performance by use of a 10.8 nm NbTiN film.…”
Section: Discussionsupporting
confidence: 78%
“…In the fabrication process of the mixer, an in-situ technique is employed to avoid the oxidation and contamination of the surface of the NbTiN film. Therefore, the optimized hot spot model incorporates in the phonon-and diffusion-cooling mechanism together [6]. In a typical HEB mixer, a microbridge is made up of an ultrathin superconducting film placed between two metal contact pads.…”
Section: Theoretical Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Two tested HEB mixers differed, not only in terms of the critical temperature, but also MgB2 film thickness. As it follows from the HEB mixer theory, and some experiments with NbTiN HEB mixers [10], the film thickness affects the GBW and NBW of the device due to a longer phonon escape time. However, it should not affect the noise temperature (at IF << GBW) unduly.…”
Section: Resultsmentioning
confidence: 96%
“…ot-electron bolometer (HEB) mixers have been proven to be a class of highly sensitive terahertz (THz) detection elements (from 1.3THz to 5.3THz) employed in many receivers for astronomical and atmospheric science observation programs launched in recent years, including RLT [1], APEX [2], [3], Herschel [4], [5], TELIS [6], [7], SOFIA [8], [9]. They are also chosen for different programs under development, such as ASTE [10], DATE5 [11].…”
Section: Introductionmentioning
confidence: 99%